Sikap Masyrakat Arab terhadap Perancis Pasca Kemunculan Karikatur Nabi Muhammad Saw dalam Majalah Charlie Hebdo Edisi September Tahun 2020: Studi Fenomenologi Edmund Husserl - Fadhilah Rahmawati (Universitas Al Azhar Indonesia, 2022)
Abstract - The purpose of this article is to describe the attitude of the Arab Arab community towards France after the appearance of the caricature of the Prophet Muhammad in the September 2020 edition of Charlie Hebdo Magazine based on the perspective of Edmund Husserl's phenomenological study. The problems that will be investigated are: (1) how did the caricature of Prophet Muhammad (PBUH) appear in Charlie Hebdo magazine?: and (2) how was the attitude of the Arab community towards France after the appearance of the caricature of the Prophet Muhammad in the September 2020 edition of Charlie Hebdo Magazine? The object studied is in the form of national and international online news media. The research method used is qualitative. Data collection using the watch and note technique. Then the data were analyzed by descriptive analysis technique. To validate the data, the technique used is the triangulation technique. The results of this research are (1) the appearance of caricatures of the Prophet Muhammad in Charlie Hebdo magazine starting in 2006 which is a reprint of the Danish magazine Jyllands-Posten. Chalie Hebdo magazine has published caricatures of the Prophet Muhammad four times in the vulnerable time between 2006 and 2020: and (2) the publication of caricatures of the Prophet Muhammad in the September 2020 edition of Charlie Jebdo magazine has raised angry attitudes from the Arab Muslim community towards Franc, through the condemnation of many countries, demonstrations of the Arab Muslim community, to the boycott of French products.Keywords – Cartoon of Prophet Muhammad, Charlie Hebdo, Arab-France Coflict, Phenomenolog